Prevalence of antibodies against Toxoplasma gondii and Neospora caninum in dogs - Langoni, Hélio [UNESP]; Fornazari, Felipe [UNESP]; Silva, Rodrigo Costa Da [UNESP]; Monti, Elis Talita [UNESP]; Villa, Fausto Baptista [UNESP] (Sociedade Brasileira de Microbiologia, 2013)
Toxoplasmosis and neosporosis are parasitic diseases of global importance. The present study had the objective to determine the influence of age, sex and breed in the prevalence of antibodies against both diseases in dogs from Brotas city, São Paulo State, Brazil. Blood samples of 342 dogs were collected, and the age, sex and breed of each animal were recorded. The serological diagnosis for toxoplasmosis and neosporosis were performed using the immunofluorescent antibody test (IFAT). The Fischer's test was used to calculate the association probability of the variables, with a = 5%. For toxoplasmosis the prevalence of antibodies was 26.9% (CI 95% 22.4-31.8%), and for neosporosis 4.97% (CI 95% 3.1-7.8%). The statistical analysis revealed a higher risk of infection for T. gondii in dogs with more than five years.
Keywords: Toxoplasma gondii; Neospora caninum; IFAT